Pilocytic astrocytoma demethylation and transcriptional landscapes link bZIP transcription factors to immune response - Aichmüller, Christian Felix; ̇Iskar, Murat; Jones, David T. W.; Korshunov, Andrey; Radlwimmer, Bernhard; Kool, Marcel; Ernst, Aurélie; Pfister, Stefan; Lichter, Peter; Zapatka, Marc (Neuro-Oncology, 2020)
Pilocytic astrocytoma (PA) is the most common pediatric brain tumor. While genome and transcriptome landscapes are well studied, data of the complete methylome, tumor cell composition, and immune infiltration are scarce.We generated whole genome bisulfite sequence (WGBS) data of 9 PAs and 16 control samples and integrated available 154 PA and 57 control methylation array data. RNA sequence data of 49 PAs and 11 control samples as well as gene expression arrays of 248 PAs and 28 controls were used to assess transcriptional activity.DNA-methylation patterns of partially methylated domains suggested high stability of the methylomes during tumorigenesis. Comparing tumor and control tissues of infra- and supratentorial location using methylation arrays revealed a site specific pattern. Analysis of WGBS data revealed 9381 significantly differentially methylated regions (DMRs) in PA versus control tissue. Enhancers and transcription factor (TF) motifs of five distinct TF families were found to be enriched in DMRs. Methylation together with gene expression data-based in silico tissue deconvolution analysis indicated a striking variation in the immune cell infiltration in PA. A TF network analysis showed a regulatory relation between basic leucine zipper (bZIP) transcription factors and genes involved in immune-related processes.We provide evidence for a link of focal methylation differences and differential gene expression to immune infiltration.
Gesehen am 12.02.2021